Mechanochemically synthesized high alumina cement and their implementation as low cement castables with some micro-fine additives - Kumar V.; Singh V.K.; Srivastava A.; Hemanth Kumar P. (My University, 2025)
High-energy ball milling viz. mechanochemical process is being utilized to mechanically activate ceramic powders for low temperature solid state reactions. The process can help to select low-cost commercially available oxides and can produce powders with nanometer size granules. On the other hand, high alumina cement provides high service temperature when used as refractory castable. Therefore, the effects of high-energy ball milling and subsequent calcinations on the formation of high alumina cementing phases using mixtures of Al 2 O 3 and CaCO 3 were investigated. Nano-meter sized high alumina cement (HAC) powders were synthesized by mechanochemical treatment of Al 2 O 3 and CaCO 3 in weight ratios 7:3 and 8:2. This paper compares the calcined high alumina cement obtained by mechanically activated precursor mix for 1, 2 and 3h. Low cement castables were prepared from calcined Chinese bauxite as aggregate matrix, prepared HAC acting as hydraulic binder and micro-fine additives as pore filling agents. The bonding of high alumina cement as well as sinterability in these castable was studied with ZrO 2 , α-Al 2 O 3 and SiC as micro-fine additives. Castables formulated by prepared high alumina cement demonstrate remarkably improved bulk density and apparent porosity as when compared with those prepared by commercially available cement. Casting water demand was also reduced, as a result quick setting behavior was observed. The addition of mechanochemically processed cements in refractory castables improved the thermo-mechanical properties to a significant extent. © 2014 The Ceramic Society of Japan and the Korean Ceramic Society.